Critical roles of the rhombohedral-phase inducers in morphotropic NaNbO3-BaTiO3-ABO3 quasi-ternary lead-free piezoelectric ceramics. Issue 16 (December 2018) - Qi, He; Zuo, Ruzhong; Li, Jing-feng; Li, Longtu
Abstract: A morphotropic phase boundary (MPB) between rhombohedral (R) and tetragonal (T) phases was identified in a few (0.9-x)NaNbO3 -0.1BaTiO3 -xABO3 (x = 0–0.05) lead-free systems. Critical roles of R-phase inducers were specially evaluated in terms of phase boundary position, microstructure and piezoelectric responses. The results indicate not only the tolerance factor of the ABO3 additive but also its ferroelectricity and corresponding volume change would influence the formation of phase boundary and further determine dielectric and ferroelectric responses. The piezoelectric coefficient d33 of MPB compositions was compared with theoretically-calculated d33-cal according to d33 = 2Pr ·ε33 ·Q33, demonstrating that the piezoelectric response of these systems should be determined by combined effects of the phase coexistence, nano-scale domains and particularly enhanced dielectric responses. The largest d33 ∼305 pC/N, the highest ε33 T /εo ∼2815 and the lowest Pr ∼14.7 μC/cm 2 were achieved in the MPB composition with 3.75% SrZrO3 . These experimental results provide a valuable reference for designing new NaNbO3 -based lead-free piezoelectric materials.